2016
DOI: 10.3233/jad-151155
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Biomarker Candidates of Cerebral Amyloid Using PiB PET in Non-Demented Elderly

Abstract: Increasingly, clinical trials for Alzheimer’s disease (AD) are being conducted earlier in the disease phase and with biomarker confirmation using in vivo amyloid PET imaging or CSF tau and Aβ measures to quantify pathology. However, making such a pre-clinical AD diagnosis is relatively costly and the screening failure rate is likely to be high. Having a blood-based marker that would reduce such costs and accelerate clinical trials through identifying potential participants with likely pre-clinical AD would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 32 publications
(34 reference statements)
1
47
0
Order By: Relevance
“…; Westwood et al . ). However, these data have not been replicated or examined in relation to neurodegenerative dementias other than AD and should presently be interpreted with caution.…”
Section: Biomarkers For Amyloid β Pathologymentioning
confidence: 97%
“…; Westwood et al . ). However, these data have not been replicated or examined in relation to neurodegenerative dementias other than AD and should presently be interpreted with caution.…”
Section: Biomarkers For Amyloid β Pathologymentioning
confidence: 97%
“…Another COU with high potential to aid in clinical trials is the identification of blood-based biomarkers that can identify those individuals with high (or low) likelihood of being amyloid positive[4042]. Westwood and colleagues[40] recently examined proteomic markers among longitudinal plasma samples collected over a 12-year period among non-demented individuals with [11C]PiB PET scans available.…”
Section: Current State Of the Sciencementioning
confidence: 99%
“…Westwood and colleagues[40] recently examined proteomic markers among longitudinal plasma samples collected over a 12-year period among non-demented individuals with [11C]PiB PET scans available. In this study, seven plasma proteins (including A2M, Apo-A1, and multiple complement proteins) were significantly associated with amyloid burden.…”
Section: Current State Of the Sciencementioning
confidence: 99%
“…To bypass the invasiveness of CSF collection, there is a strong interest in finding blood-based markers that yield the same information about amyloid status as would be obtained from CSF. There have been a number of studies which have shown that a blood protein signature can be found that reflects AD brain pathology as measured by PET [15][16][17][18][19][20][21][22][23][24] . Of particular interest is the recent study by Nakamura et al (2018) 25 , whereby levels of Aβ 1−40 , Aβ 1−42 and APP 669−771 in plasma, measured using specialised immunoprecipitation (IP) coupled with Matrix Assisted Laser Desorption/Ionization (MALDI) time-of -flight (TOF) mass spectrometry (MS) (henceforth referred to as IP-MALDI-TOF-MS), were shown in combination to have strong performance (> 0.94 area under the receiver operating characteristic curve (AUC)) in predicting PET Aβ 1−42 status across two cohorts.…”
Section: Introductionmentioning
confidence: 99%